WAYS OF IMPROVING TRADE IN JORDAN WITHIN THE FRAMEWORK OF INTERNATIONAL COMMERCIAL LAW - Farouq Ahmad Faleh Alazzam (Фінансово-кредитна діяльність: проблеми теорії та практики)
The main purpose of the article is to identify ways to improve the trading system in the framework of the development of international commercial law. The object of research is the trading system and commercial law in Jordan. The scientific task is to form a model for improving the trading system in the framework of the development of international commercial law in Jordan. The main method used in the article is the IDEF3 method, which allows, through a system of flowcharts, to model the directions for improving the trading system in the framework of the development of international commercial law. As a result of the study, the key stages of improving the trading system in Jordan in the framework of the development of international commercial law were identified and characterized, including the use of digital technologies, the expansion of rights and freedoms in trade, and the use of smart contracts. The value of the obtained results lies in modelling and improving the efficiency of trade operations in Jordan taking into account the norms and rules of international commercial law. The limitations of the study concerned taking into account the specifics of trade and law only in Jordan because the author of the article belongs to this country.